ESTIMATES ON MEDICATION COST OF DRUG DOSE SPECIFIC TREATMENT PROTOCOL FOR HYPERTENSION MANAGEMENT IN PUBLIC AND PRIVATE HEALTHCARE SECTORS IN INDIA. (June 2022) - Sahoo, Swagata Kumar; Pathni, Anupam Khungar; Krishna, Ashish; Sharma, Bhawna; Cazabon, Danielle; Moran, Andrew E.; Hering, Dagmara
Abstract : Objective: Hypertension is a major public health challenge in most low- and middle-income countries and calls for prioritization of large-scale hypertension control programs. Adoption of drug and dose specific treatment protocols as recommended by the WHO-HEARTS is crucial for scaling up effective hypertension treatment in resource-limited settings. This study estimated the annual cost of medication per patient using three such protocols in India. Design and method: The medication requirement was simulated with a range of hypertension control assumptions for the selected protocols based on preliminary observations from sentinel sites of a large-scale hypertension control program in the public sector. Two five-step single molecule and a single pill combination (SPC) based antihypertensive treatment protocols were selected for this study and the approximate medication costs was calculated based on Indian prices in the public and private sectors. Result: The approximate annual cost of antihypertensive medication per patient ranged from $33.88–58.44 in the private sector when using a single molecule drug protocol and from $51.57–68.83 when using a SPC drugs protocol. The cost of medication was lower in the generic stores ranging between $5.78–9.57 for single molecule protocols and $7.35–9.89 for protocol with SPC. The cost of medication for patients covered by the public sector was the lowest at $2.05–3.89 for single molecule protocols and $2.94–3.98 for SPC. Conclusion: At less than $4 per patient per annum, scaling up hypertension control program with drug and dose specific treatment protocols is a potentially cost-effective public health intervention to save lives and reduce expenses associated with cardiovascular complications in India. Generic drug prescription enforcement and the development of low-cost generic retail networks would increase affordability in the private sector. The cost of treatment with SPCs is comparable to the single molecule protocol, and therefore SPC based treatment protocol can be adopted in a public health program considering the advantage of simplified logistics, reduced pill burden, improved treatment adherence and blood pressure control.